The effects of avoiding extended antimicrobial drain prophylaxis on Clostridioides difficile and postprocedural infection rates: a 5-year retrospective - Marino, Alexandria C; Robinson, Evan D; Durden, Jakob A; Cox, Heather L; Mathers, Amy J; Shaffrey, Mark E (Journal of neurosurgery, 2022)
Postprocedural infection is a consequential complication of neurosurgical intervention. Periprocedural antimicrobial prophylaxis is routinely administered to prevent infection, and in some cases, continued for extended periods while surgical drains remain in place. However, there is little evidence that extended antimicrobial administration is necessary to reduce postprocedural infection, and extended antimicrobials can be associated with harm, such as Clostridioides difficile infection. The authors sought to evaluate whether shortening the duration of postprocedural antimicrobial prophylaxis would decrease the incidence of C. difficile infection without increasing the incidence of postprocedural infection. In this retrospective study, two general neurosurgical cohorts were examined. In one cohort, postoperative antimicrobial prophylaxis was limited to 24 hours; in the other, some patients received extended postoperative antimicrobial prophylaxis while surgical drains or external ventricular drains (EVDs) remained in place. Rates of infection with C. difficile as well as postprocedural infection after surgery and EVD placement were compared. Seven thousand two hundred four patients undergoing 8586 surgical procedures and 413 EVD placements were reviewed. The incidence of C. difficile infection decreased significantly from 0.5% per procedural encounter to 0.07% with the discontinuation of extended postprocedural antibiotics within 90 days of a procedure. Rates of postprocedural infection and EVD infection did not significantly change. Results were similar in subgroups of patients with closed suction drains as well as cranial and spine subgroups. Discontinuation of extended antimicrobial prophylaxis was associated with a significant decrease in the incidence of C. difficile infection without a concomitant change in postprocedural infections or EVD-associated infection. This study provides evidence in support of specialtfy-wide discontinuation of extended postoperative antimicrobial prophylaxis, even in the presence of closed suction drains.